Experiences of nursing students who are victims of dating violence: a qualitative study - Esperanza Barroso-Corroto; José Alberto Laredo-Aguilera; Ana Isabel Cobo-Cuenca; Juan Manuel Carmona-Torres (BMC, 2024)
Abstract Background Dating Violence (DV) is a type of Intimate Partner Violence that occurs between young people, and they are those behaviours that cause physical, sexual or psychological harm. Objective/aim To know the experience of university students around dating violence. Design and methods Qualitative study with a phenomenological approach was conducted through semi-structured individual interviews with nursing students' victims of dating violence with the same starting categories. The public involve in this study were nursing students who freely agreed to participate in the interviews and gave their informed consent. Results Eleven nursing students participated, the sample was heterogeneous for gender and sexual diversity. Obtaining results about their experience with dating violence, manifestations of dating violence and cyber violence in their relationships, consequences, formal and informal help seeking and proposals for help as nursing students, among others. Conclusion Dating violence is a serious problem that seriously affects the victims and requires the creation of prevention programs. The experiences of university students about DV are mainly painful experiences, with serious consequences for those involved, needing help from their close environment and professional help to overcome the problems generated by their partners. Implications It is important due to the high prevalence of this phenomenon, also among nursing students, to provide key points to future health professionals and victims of dating violence on the correct way to act against violence due to lack of knowledge on the subject. This study clarifies the experiences of dating violence and how to offer help to victims from the informal and professional sphere. Trial registration This study was approved by the Ethics Committee of Clinical Research of the Health Area of Talavera de la Reina (Toledo) with code 01/2021.